Graphic recognition : current trends and challenges : 11th International Workshop, GREC 2015, Nancy, France, August 22-23, 2015, Revised selected papers /: current trends and challenges : 11th International Workshop, GREC 2015, Nancy, France, August 22-23, 2015, Revised selected papers. (2017) - Unknown
No abstract available